1999
DOI: 10.1074/jbc.274.22.15389
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of Protein Kinase Cε and Protein Kinase Cδ to Membrane Is Required for Ultraviolet B-induced Activation of Mitogen-activated Protein Kinases and Apoptosis

Abstract: UV-induced signal transduction may be involved in tumor promotion and induction of apoptosis. The role of protein kinase C (PKC) in UVB-induced signal transduction is not well understood. This study showed that UVB markedly induced translocation of membrane-associated PKC⑀ and PKC␦, but not PKC␣, from cytosol to membrane. Dominant negative mutant (DNM) PKC⑀ or PKC␦ inhibited UVB-induced translocation of PKC⑀ and PKC␦, respectively. UVB-induced activation of extracellular signal-regulated protein kinases (Erks)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
109
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(116 citation statements)
references
References 44 publications
5
109
2
Order By: Relevance
“…The In many cells including keratinocytes, UVB irradiation-induced apoptosis depends on p38 [9,17,31]. Still UVB-induced activation of ERK and JNK has been reported in normal human keratinocytes and in HaCaT cells [24].…”
Section: Discussionmentioning
confidence: 99%
“…The In many cells including keratinocytes, UVB irradiation-induced apoptosis depends on p38 [9,17,31]. Still UVB-induced activation of ERK and JNK has been reported in normal human keratinocytes and in HaCaT cells [24].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of cells to C2-ceramide induced dose dependent activation of JNK . In addition, UVB-induced activation of ERK and JNK was strongly inhibited by dominant negative mutant of PKCe and PKCd (Chen et al, 1999a). Recently, a line of evidence showed that inhibition of ERK activation blocked UVB induced AP-1 activation in mouse epidermal cells, and over expression of ERK restored UV responsiveness, indicating that ERK was necessary for UVB induced AP-1 activation (Huang et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This contention is supported by findings that dPKC plays a central role in the regulation of cell apoptosis in response to a large and diverse array of apoptotic stimuli (Brodie and Blumberg, 2003). For example, during the initiation of apoptosis, dPKC has been shown to translocate from cytosol to a variety of cellular organelles including mitochondria (Mochly-Rosen, 1995;Sawai et al, 1997;Chen et al, 1999;Dal Pra et al, 1999;Li et al, 1999;Dempsey et al, 2000;Majumder et al, 2000). Also, we recently demonstrated in an in vitro study that increased dPKC translocation correlated with neuronal death in CA1 region of hippocampus, implying a definite role of dPKC in neuronal death (Bright et al, 2003(Bright et al, , 2004.…”
Section: Introductionmentioning
confidence: 95%